Eksplorasi Kritis Literasi Digital: Analisis Dekonstruksi Teks Berita Hoaks Oleh Siswa Kelas Ix Smp Negeri 11 Bengkulu Tengah Dalam Pembelajaran Kritis - Ayu Lestari, Puspita; Salamah; Putri Juni Astuti, Dina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to investigate students’ critical digital literacy skills through the deconstruction of hoax news texts within a critical learning framework. The research focuses on how ninth-grade students at SMP Negeri 11 Bengkulu Tengah uncover internal contradictions, ideological biases, and linguistic manipulation contained in fake news circulating on social media. The method used is qualitative descriptive with a case study approach. Data were collected through a news deconstruction portfolio test, participatory observation of the learning process, and structured in-depth interviews with nine student informants and an Indonesian language teacher. Data analysis applied a critical discourse analysis model integrated with Derridean deconstruction methods, including the identification of binary consistencies, the tracing of ambiguities (aporia), and the reversal of textual hierarchies. The results of the study indicate that at the beginning of the learning process, students were trapped in passive-literal reading due to low functional digital literacy. However, after being intervened with a deconstruction-based critical learning model, students began to be able to identify factual inconsistencies, trace information sources, and uncover the persuasive rhetoric used by hoax producers. However, after being exposed to a deconstruction-based critical learning model, students began to identify factual inconsistencies, trace information sources, and uncover the persuasive rhetoric used by hoax creators. The main challenges faced by students included limited critical thinking skills, digital conformity bias (echo chambers), and a reliance on emotional intuition rather than logical verification. This study concludes that text deconstruction effectively serves as a pedagogical tool to transform students from vulnerable consumers into critical and emancipatory agents of information literacy.